The Influence of Mount Sepikul Natural Tourism on Socio-Economic Conditions in Tiyaran Village - Marchelina Dwi Hapsari; Akhmad Arif Musadad (Historia, 2027)
This study analyzes the management of the Gunung Sepikul natural tourist attraction in Tiyaran Village and its implications for the socioeconomic conditions of the local community. Using a qualitative methodology, data were collected through in-depth interviews, observations, and document reviews involving the village government, POKDARWIS, Karang Taruna, and tourists. Historically, the transformation of this area from agricultural land into a tourist destination was driven by the community’s demographic characteristics, which allowed for adaptability to changes in land use. The study’s findings indicate a synergy among stakeholders within a community-based management model, where the involvement of the productive-age group serves as the cornerstone of environmental conservation. Tourists are drawn to visit Gunung Sepikul due to its unique natural aesthetic appeal and the widespread availability of information via social media. This has significantly impacted improved well-being through the creation of jobs and new business opportunities, although the majority of these remain in the informal sector. However, limitations in infrastructure and service standardization remain challenges that need to be addressed through integrated community capacity-building. Overall, optimizing local participation is the key to ensuring inclusive and sustainable tourism growth in the future.